Thank you for the opportunity to help you with your question! the solution is as such:

for a spring F= k (xf - xi)

where

F is the force applied.

k is the spring constant

(xf - xi) is the elongation

so when xi= 67.3m and xf = 70.8m

and F = m*g (i.e. weight of jumper)

= 59.3* 9.8

= 581.14 N

so k= F / (xf - xi)

= 581.14 / 3.5

k= 166.04 N/m

so the spring constant k = 166.04 N/m

now when k = 166.04 N/m

F= m*g

= 57.9* 9.8

F = 562.52 N

and xi = 67.3 m

then xf= ?

from, F= k (xf - xi)

xf - xi = F/k

= 562.52 / 166.04

= 3.387

so xf = xi + 3.387

xf = 70.68m

so the final elongation is 70.68m

Please let me know if you need any clarification. I'm always happy to answer your questions.awaiting a positive feedback. It was lovely helping you. Looking forward to help you again. A positive feedback awaited thank you.